Peran Hukum dalam Mengamati Keluarga terhadap Pembentukan Kepribadian Individu - Egas, Egas; Amalia, Mia; Mulyana, Aji (Jurnal Parenting dan Anak, 2024)
The family has a central role in shaping an individual's personality and character. The family environment, as the first educational institution, provides the basis for social interaction, behaviour, and understanding of social norms. Good parenting patterns support the formation of a positive personality, while poor parenting patterns can result in deviant behaviour in adolescents. This research aims to identify the role of law in observing the influence of the family on the formation of individual personalities. The research method uses a qualitative and normative juridical approach by referring to previous literature. The results of the discussion show that the family has a significant impact on personality formation, and the law has an important role as an instrument of supervision. However, the implementation of the role of law is not yet fully effective, especially in the context of education and parenting programs. Increasing access to education, strengthening parenting programs, and improving legal regulations are the keys to forming a quality generation. Therefore, this research highlights the important role of the family, as well as the need for improvements in the legal and educational systems to support the vision of Indonesia 2045.